Design of Bacterial Foraging Interval Fuzzy Logic Controller on Hybrid Solar Tracker-Ocean Wave Energy Converter - Dwi Nur Fitriyanah; Imam Abadi (IPTEK The Journal of Engineering, 2021)
The location of Indonesia which, is crossed by the equator, makes it rich in sunlight. Photovoltaic (PV) can convert solar energy into electrical energy. The Solar Tracker system can maximize the absorption of solar energy that enters the PV. The condition of the Indonesian archipelago also has the potential for ocean wave energy. The Hydrostatic transmission-based Wave Energy Converter system can convert ocean wave energy into electrical energy. This research combines two energies, namely solar energy and ocean waves. The importance of combining these two renewable energies is due to the non-continuous nature of solar energy, therefore combined with the ocean wave energy to maximize the energy produced. A type-2 fuzzy logic control system based on Bacterial Foraging Optimization (BFO) is applied to each converter, summing each converter that has been optimizing. Optimize error and delta error on the solar tracker system and fuzzy logic waveform-based sea-wave type-2 system. The fuzzy boundaries are then optimized using the BFO optimization method. Fuzzy type-2 based on BFO in solar tracking system can increase energy by 67.9% with the best performance at FOU ±0.1. BFO-based type-2 fuzzy control can stabilize the output of the ocean wave conversion system and produce average energy of 34.48 Wh. This research can increase the energy in the system after being optimized using BFO by 19.3%.